2019
DOI: 10.1007/s13197-019-03669-x
|View full text |Cite
|
Sign up to set email alerts
|

Duck egg albumen: physicochemical and functional properties as affected by storage and processing

Abstract: The demand for duck meat and eggs in Asian countries increases every year. Duck egg albumen has become an important ingredient in the food industry alongside its hen counterpart, because of its excellent nutritive and functional properties. The major proteins in duck albumen are ovalbumin, ovomucoid, ovomucin, conalbumin, and lysozyme. Comparing with hen albumen, lower contents of ovalbumin, conalbumin, lysozyme and ovoflavoprotein are found in duck albumen. Nevertheless, duck albumen shows better gelling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 80 publications
1
30
0
Order By: Relevance
“…Some studies have been conducted on the interaction system between EGCG and proteins. Quan and Benjakul found that the conjugate between duck albumen hydrolysates and EGCG could serve as an antioxidant emulsifier; Cao and Xiong reported that EGCG has caused significant structural changes and induced great digestibility of whey protein isolate, reducing its total sulfhydryl content and surface hydrophobicity; Kanakis et al . found that EGCG has a high binding affinity to whey proteins due to galloyl functional group with multiple peptide binding sites, able to form hydrophobic interactions and hydrogen bonds with the proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been conducted on the interaction system between EGCG and proteins. Quan and Benjakul found that the conjugate between duck albumen hydrolysates and EGCG could serve as an antioxidant emulsifier; Cao and Xiong reported that EGCG has caused significant structural changes and induced great digestibility of whey protein isolate, reducing its total sulfhydryl content and surface hydrophobicity; Kanakis et al . found that EGCG has a high binding affinity to whey proteins due to galloyl functional group with multiple peptide binding sites, able to form hydrophobic interactions and hydrogen bonds with the proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Egg white protein (EWP) is composed mainly of ovalbumin (OVA), ovotransferrin (OVT), ovomucoid (OVM), ovomucin (OVN), and lysozyme (LYZ) (Quan & Benjakul, 2019). OVA is the monomer phosphorylated glycoprotein containing free sulfhydryl groups in EWP.…”
Section: Egg White Proteinmentioning
confidence: 99%
“…Duck eggs are rich in proteins (1.0 mg/g), essential amino acids (46 mg/g), cholesterol (1.1 mg/g), minerals (5.5 mg/g), vitamins (4.9 mg/g), and other nutrients ( Friday, 2011 ; Sun et al, 2019 ). The storage life of duck egg is < 40 days at room temperature (25 °C) and <90 days at cool temperature (4 °C) ( Quan and Benjakul, 2019 ). In the market, duck eggs mainly exist in two forms: (1) Dark duck eggs; and (2) clean duck eggs.…”
Section: Introductionmentioning
confidence: 99%